Comparison of the Results Synchronization with Progesterone Implants and Fixed Time Artificial Insemination in Dairy Cows - Arkose,Cem Cagdas (2022)
Abstract Dairy cows that are being cared for in family businesses were used to compare the pregnancy rates by applying different time periods, using progesterone devices, and using fixed-time artificial inseminations. The cows were randomly divided into 3 groups. Group 1(n = 56); On day 0, GnRH (IM) (10mg Buserelin acetate, Ovarelin, CEVA DIF) + Progesterone implants (PRID®) (1,55 g progesterone CEVA), Day 8 PGF2α (Dinoprost tromethamine, 25 mg, Dinolytic, Pfizer), Day 9 Progesterone implants removal + PGF2α, insemination was performed at 56th hours insemination after the second PGF2α injection. Group 2 (n = 50); on day 0, GnRH (IM) + Progesterone implants, PGF2α (IM) on the 8th day, Progesterone implants removal + PGF2α on the 9th day, insemination was performed at 48th and 72th hour after the second PGF2α injection. Group 3 (n = 53); on day 0 GnRH (IM) + Progesterone implants, on the 5th day PGF2α injection, day 6 PGF2α (IM) and remove progesterone implant and insemination at 56 hours after the second PGF2α. The average milk yield was recorded Group 1 16.66 ± 5.28 kg, Group 2 13.46 ± 3.05 kg. and Group 3 was recorded as 15.35 ± 4.60 kg. Pregnancy diagnoses were performed 35 days after the artificial insemination. The pregnancy rate was 41.07% in Group 1, 42% in Group 2, and 52.83% in Group 3. As a result; pregnancy rates were similar in all three groups. It has been concluded that synchronization with progesterone can solve many reproductive problems.